Adrenal Gland Dysfunction and Its Link to Endocrine Disorders: Disfungsi Kelenjar Adrenal dan Kaitannya dengan Gangguan Endokrin - Duaa Hamad Hamza (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The adrenal glands, also known as suprarenal glands, are vital endocrine organs located above each kidney. Specific Background: Comprising the cortex and medulla, these glands produce a variety of hormones essential for metabolic regulation, immune response, stress adaptation, and cardiovascular function. Knowledge Gap: Despite extensive research on adrenal hormone synthesis, a comprehensive understanding of how structural and functional alterations in these glands contribute to various endocrine disorders remains limited. Aims: This study aims to elucidate the correlation between adrenal gland composition, hormone secretion, and the manifestation of adrenal-related diseases. Results: Findings demonstrate that the adrenal cortex synthesizes steroid hormones—mineralocorticoids, adrenal androgens, and glucocorticoids—while the medulla produces catecholamines such as epinephrine and norepinephrine. Dysregulation in hormonal output is linked to disorders including Addison’s disease, Cushing’s syndrome, congenital adrenal hyperplasia, primary aldosteronism, and adrenal cancers. Novelty: This study provides an integrated perspective on the structural-functional relationship of the adrenal gland and its role in disease etiology. Implications: Understanding these mechanisms enhances diagnostic and therapeutic strategies for managing endocrine disorders associated with adrenal dysfunction. Highlights: Adrenal glands regulate vital hormones for body homeostasis. Dysfunction causes Addison’s, Cushing’s, and adrenal-related diseases. Insights aid diagnosis and treatment of endocrine disorders. Key words: Adrenal gland structure , Corticosteroids, Catecholamines, Adrenal gland disorder